Community’s Knowledge of COVID-19 and Its Associated Factors in Mizan-Aman Town, Southwest Ethiopia, 2020 - Mechessa DF; Ejeta F; Abebe L; Henok A; Nigussie T; Kebede O; Mamo Y (International Journal of General Medicine, 2020)
Desalegn Feyissa Mechessa,1 Fikadu Ejeta,1 Lemi Abebe,2 Andualem Henok,2 Tadesse Nigussie,2 Oliyad Kebede,1 Yitagesu Mamo1 1Department of Pharmacy, College of Medicine and Health Science, Mizan-Tepi University, Mizan-Aman, Ethiopia; 2Department of Public Health, College of Medicine and Health Science, Mizan-Tepi University, Mizan-Aman, EthiopiaCorrespondence: Desalegn Feyissa Mechessa Tel +251917127556Email sinaawayya@gmail.comBackground: Coronaviruses are a large group of viruses that are common throughout the community. They are associated with mortality, hospitalization, substantial extra costs and lower patient’s quality of life. Thus, this study aimed to assess the community’s knowledge of COVID-19 and associated factors in Mizan-Aman town, southwest Ethiopia.Methods: Community-based cross-sectional study design was conducted among the community of Mizan-Aman from April 14 to May 14, 2020. A systematic sampling technique was used to collect data from selected households. Data were entered into Epi data version 4.0.2.101 and then exported to SPSS version 24.0 for analysis. To identify the predictors of knowledge of COVID-19, multiple backward logistic regression analysis was used. To show the accuracy of data analysis, 95% CI was used, and statistical significance was considered at p < 0.05.Results: From 423 sampled population, 393 (92.9%) of them responded to the questionnaire. Of these, 233 (59.3%) were male, 225 (57.3%) were 18– 34 years old, and 250 (63.6%) were married. The overall correct rate of the knowledge questionnaire was 74.75%. More than 85% of respondents were well aware of the main clinical symptoms of COVID-19, its transmission by close contact, its prevention by not going to crowded places and isolation of infected persons. Male gender (AOR=3.74, CI: 1.87– 7.49), age (35– 54 years) (AOR=3.81, CI: 1.35– 10.70), age ≥ 55 (AOR=2.97, CI: 1.16– 7.62), lack of formal education (AOR=6.0, CI: 1.54– 23.40), farmer (AOR=8.72, CI: 2.08– 35.53), daily laborer (AOR=7.57, CI: 2.28– 25.15), merchant (AOR=6.34, CI: 2.06– 19.43), house wife (AOR=11.59, CI: 2.91– 46.23) were significantly associated with poor knowledge, whereas single marital status was less likely associated with poor knowledge of COVID-19.Conclusion: One-third of the study participants had poor knowledge regarding COVID-19. Male gender, age above thirty-five years, lack of formal education, being farmer, daily laborer, merchant and house wife were significantly associated with poor knowledge. Therefore, awareness creation should be given.Keywords: community’s, COVID-19, knowledge, Mizan-Aman, southwest Ethiopia